MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KEUNGGULAN KOMPETITIF DI SEKOLAH MENENGAH KEJURUAN NEGERI 7 - Julia; Kholid Ansori (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
This study aims to describe the application of human resource management (HRM) to enhance competitive advantage at State Vocational High School (SMKN) 7 Batang Hari. This study used a qualitative descriptive approach with field study methods. Data were collected through interviews, observations, and documentation with the principal and teachers as the primary sources. The results indicate that human resource management at SMKN 7 Batang Hari is implemented through the process of planning teaching staff needs, placing teachers according to competency, implementing academic supervision, and fostering discipline and work motivation. These efforts strengthen a culture of professionalism and responsibility among teachers, which has implications for improving the quality of learning and the school's reputation.